A Paradigm for Developing Better Measures of Marketing Constructs - Churchill, Gilbert A. (Journal of Marketing Research, 1979)
A critical element in the evolution of a fundamental body of knowledge in marketing, as well as for improved marketing practice, is the development of better measures of the variables with which marketers work. In this article an approach is outlined by which this goal can be achieved and portions of the approach are illustrated in terms of a job satisfaction measure.